The role of the mosque as a social and community building institution : a case study of Masjid Sultan Muhammad III, Pasir Mas, Kelantan / Noor Nurul Ashraq Abdul Razak - Noor Nurul Ashraq, Abdul Razak (2020)
One of the issues addressed today was the issue of the role of mosques in society. There are various perceptions of Muslims in this country about the functioning of mosques. Among these are the mosque's only views on worship, especially in the prayers of both the congregation and the individual. This explains how a mosque can attract visitors to the mosque through aspects of attraction such as the location of the mosque itself, the location of the place of worship, the state of the facilities in the mosque, the concept and architecture of the mosque as well as the activities carried out in the mosque . In addition, this study will see to what extent the rooms in the mosque meet the mosque's requirement to visit the mosque. This study also seeks to see the value of the mosque's response to the various aspects of the mosque's attraction as it serves as a religious center, a knowledge center, a center for community activities and thus fulfills the demands of today's social development.